PERAN BADAN KEATUAN BANGSA DAN POLITIK KABUPATEN BENGKALIS DALAM MEWUJUDKAN PARTISIPASI POLITIK YANG CERDAS DAN BERINTEGRITAS TAHUN 2018 - Deswanda, Iko; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
To realize smart political participation and have Body integrity to Unity of Nation and Politics have to play its role as government agency to be target of which is dreamed of is immediately reached. Role represent attitude consciously which must be taken by governance institution to reach for especial target, policy, and or actions into related/relevant inwroughtly. Formula of is Problem of the taken is How Effort Body Unity of Nation and Politics Sub-Province of Bengkalis In Realizing Smart Participation and have Integrity to year 2018 and What becoming factor resistor of Body Unity of Nation and Politics Sub-Province of Bengkalis In Realizing Smart Participation and have Integrity to year 2018.Intention of this first research for the mendeskripsikan of Role Of Body Unity of Nation and Politics Sub-Province of Bengkalis in realizing Smart Political participation and have Integrity to year 2018. Secondly to know factors pursuing Political participation storey;level exist in Sub-Province of Bengkalis. Method Research the used is Research Qualitative. this Descriptive Type Research Qualitative. this Location Research in Body Unity of Nation and Politics Sub-Province of Bengkalis. Technique data collecting by Observation, Interview, bibliography study and of study documentation. Technique analyse data by data discount, presentation of data verification and data.Result of from research show it him to realize smart participation and have integrity to use poin beberarapa Role of Government of public road which must by Body Unity of Nation and Politics Sub-Province of Bengkalis. Governmental Perann as Exponent of yaiu by running to shar workplan which have been specified by Body Unity of Nation and Politics like: Monitoring General election of Governor of Riau and Socialization To Society at General election of Governor of Riau and Role of Government as executor alone by resource mengoptimalisasi like Human Resource, Resource of Finansial and facilities and basic facilities. For the factor of resistor in realizing smart political participation and have integrity to is the limited resource and various factor of eksternal itself kesbangpol is geographical position separated by island, cultural of politics exist in Bengkalis kabpaten, difference each;every district, economic factor and storey;level education of society.Keyword: Role Of Government, Political Participation, Smart and have Integrity.